Factors Associated With COVID-19 Non-Vaccination in Switzerland: A Nationwide Study - Serena Sabatini; Marco Kaufmann; Marta Fadda; Stefano Tancredi; Nazihah Noor; Bernadette W. A. Van Der Linden; Stéphane Cullati; Stéphane Cullati; Irene Frank; Gisela Michel; Erika Harju; Erika Harju; et al. (Frontiers Media S.A., 2023)
Objectives: We compared socio-demographic characteristics, health-related variables, vaccination-related beliefs and attitudes, vaccination acceptance, and personality traits of individuals who vaccinated against COVID-19 and who did not vaccinate by December 2021.Methods: This cross-sectional study used data of 10,642 adult participants from the Corona Immunitas eCohort, an age-stratified random sample of the population of several cantons in Switzerland. We used multivariable logistic regression models to explore associations of vaccination status with socio-demographic, health, and behavioral factors.Results: Non-vaccinated individuals represented 12.4% of the sample. Compared to vaccinated individuals, non-vaccinated individuals were more likely to be younger, healthier, employed, have lower income, not worried about their health, have previously tested positive for SARS-CoV-2 infection, express lower vaccination acceptance, and/or report higher conscientiousness. Among non-vaccinated individuals, 19.9% and 21.3% had low confidence in the safety and effectiveness of SARS-CoV-2 vaccine, respectively. However, 29.1% and 26.7% of individuals with concerns about vaccine effectiveness and side effects at baseline, respectively vaccinated during the study period.Conclusion: In addition to known socio-demographic and health-related factors, non-vaccination was associated with concerns regarding vaccine safety and effectiveness.